Development of Module Early Childhood Education Based on Panca Amal Al-Washliyah to Improve Teacher's Pedagogic Competence in RA Al-Washliyah Kisaran Kabupaten Asahan Sumatera Utara - Mhd Habibu Rahman; Maemonah Maemonah (Pusat Penerbitan Universitas (P2U) Unisba, 2019)
The purpose of this study was to develop a PAUD module based on the Panca Amal Al-Washliyah, and to find out its effectiveness in improving teacher pedagogical competence at RA Al-Washliyah Kisaran. This type of research is research and development (R & D). The development process includes planning, design, and development. Product validation was carried out by media experts, material experts, Al-Washliyah administrators, and colleagues. The results of the study indicate that the product developed is feasible to be used as an independent learning media that can be used by educators. This is based on the overall assessment score of the validator, namely media experts, material experts, Al-Washliyah administrators, and colleagues who have been converted in interval data to produce positive gradients. Furthermore, based on the results of the pretest with scores of 12.25 and posttest of 25.50, there was an increase in knowledge of pedagogic competencies of 13.25 with a standard gain of 0.76 which was in the